Design and Validation of AR- Based Learning Tool Integrated with Deep Learning Approach for Secondary EFL Learners - Wa Ode Sinta Kalsum; Sariyatun Sariyatun; Nur Arifah Drajati (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study designed and validated an Augmented Reality (AR)–based vocabulary learning tool integrating deep learning pedagogy for secondary EFL learners in under-resourced contexts. Using a Research and Development approach within the ADDIE model (Analyze, Design, Develop), the Research collected data from classroom observations, needs-analysis questionnaires, and expert validation by media and subject-matter specialists. An offline-capable mobile AR prototype was developed to address infrastructural constraints and to provide contextualized vocabulary presentation, guided attention, and reflection to support mindful learning, authentic AR visualization for meaningful learning, and interactive quizzes to foster joyful learning. Expert validation indicated high feasibility and validity: media expert mean = 86.67% (very feasible) and Material expert mean = 93.72% (very valid). Collectively, these findings provide robust empirical evidence that the media is pedagogically grounded, technically feasible, and aligned with curriculum objectives. The study contributes a validated instructional design framework that demonstrates how AR can be operationalized to embody mindful, meaningful, and joyful learning principles, offering practical guidance for educators and developers seeking accessible, context-responsive vocabulary-learning solutions in marginalized EFL settings.